Evaluation of the effect of R&D subsidies on Iranian firms' innovative behavior: Reconceptualizing behavioral additionality. Issue 1 (23rd August 2019) - Soltanzadeh, Javad; Elyasi, Mehdi; Ghaderifar, Esmaeil; Rezaei Soufi, Hojat; Khoshsirat, Mohsen
Abstract : Purpose: The purpose of this paper is to evaluate the effect of government intervention on a firm's innovation activities. Design/methodology/approach: On the basis of previous literature, this paper proposes a framework to explain behavioral changes in the firm resulting from government interventions. Using propensity score matching technique, this research tries to estimate the effect of R&D subsidies on Iranian firms (small and medium-sized enterprises and large-sized firms). Findings: This paper identified that R&D subsidies have a significant effect on the innovation process. Furthermore, investigations indicate that behavioral variables (innovation capabilities, collaboration agreements and risk-taking) have been partly changed in both SMEs and large firms after subsidizing. The analysis of innovation outputs showed that although R&D subsidies significantly increase the number of new products/services or patents (especially for SMEs), it could not increase the total sale of the firms. These results show that the effect of R&D subsidies has not interestingly covered all variables influencing innovation activities. Research limitations/implications: The work used dynamic capability theory, transaction cost theory and behavioral theory of the firm to explain behavioral changes in the firm resulting from government interventions. Practical implications: This paper proposes several policy concerns which can help the policymakers to stimulate the innovation support procedures in Iran. Social implications: This paper provides insights for improved policymaking which in turn can aid boosting social welfare. Originality/value: This paper re-conceptualized behavioral additionality based on firms' behavioral theories and evaluated the effects of Iranian R&D subsidies on their measures.